Strategi Mengatasi Kesulitan Belajar Membaca Al-Qur'an dengan Metode Active Learning di Kelas VIII SMP Muhammadiyah 5 Surakarta Tahun Akademik 2015-2016 - Lestari, Rohmi; , Drs. Zaenal Abidin, M.Pd (2016)
Learning Islamic religious education is an effort to make the learners can Learn, and driven to learn. The problem facing the education world nowadays is a symptom about learning difficulties experienced by some students. A factor that is consideret special psychological syndrome is that of learning disability. Syndrome which means a symptom that appear most indicator psychic who pose learning difficulties. Symptoms found in this field are the symptoms of learning disabilies. Researcher examined the Strategies of Overcoming the Learning Difficulties in Read theAl-Qur'an with the Active Learning Methods in Class VIII Muhammadiyah Junior High School No.5 at Surakarta Academic year 2015/2016. Formulation of the problem in this is a researcher in the difficulty of what is natural in the junior high school student of Muhammadiyah Junior High SchoolmNo.5 at Surakarta learning to read Al-Qur'an and causes of learning difficulties facing learners. The type of research that researchers us qualitative research was meticulous. Methods of data using interviews, observation, and analysis of data are qualitative descriptive consisting of three lines of data reduction activities, presentation of data, and the withdrawal. Research and analysis of the data can be deduced learning difficulties include the lack of applying the science of tajwid, undertrained read the letter Hijaiyah, the fear of the teachers supervising, the lack of students ability in impersonating the letters hijaiyah. As for the cause of learning difficulties experienced by students in junior high school the Muhammadiyah Surakarta 5 include: schedule a lesson less conducive, lack of awareness of learners in reading the Qur'an, the level of intelligence of the child under the standard, family factor, less environmental support, the lack of habit of reading Qur'an, children's educational background that varies. The strategy of overcoming difficulties learning to read Al-Qur'an is through peer tutor recruitment, demonstrating the readings of the Qur'an recitation, opening the appropriate extra reading Qur'an, do exercises to students, and to give motivation to students.